Physiological and phylogenetic studies of thermophilic, hydrogen and sulfur oxidizing bacteria isolated from Icelandic geothermal areas - Hildur Vésteinsdóttir (2008)
Four thermophilic hydrogen oxidizing bacteria were isolated from various hot-springs in Grensdalur, Hveragerði, SW-Iceland. The strains were investigated with respect to phylogenetics, physiology, hydrogen uptake rates, biomass yield and sulfur metabolism. Phylogenetic studies of the isolates were done with both partial and full 16S rRNA analysis. Two true thermophilic strains were isolated, strain 16A and D10 growing optimally at 70 - 75°C, closely related to Hydrogenobacter species, showing 96% and 95% homology with Hydrogenobacter hydrogenophilus, respectively. The strains were cultivated under hydrogen oxidizing- (HOX), sulfur oxidizing- (SOX) and both hydrogen and sulfur oxidizing- (HOX+SOX) conditions. Kinetics of hydrogen oxidation, sulfate formation and generation times were investigated under all growth conditions. Both of the true thermophilic strains could grow under HOX conditions and are potential candidates for single cell protein production. In addition both strains were sulfur oxidizers and produced sulfate as end product which resulted in a low pH at the end of the experimental times. During both HOX and SOX conditions, a simultaneous oxidation of both hydrogen and thiosulfate occurred, although at lower rate compared to pure HOX and SOX conditions. The other strains isolated were moderate thermophiles. Strain 16C was identified as new species within the genus Hydrogenophilus, most closely related to H. thermoluteolus (95.6%) and strain 6C was identified as new species within the genus Thiomonas closely related to Tm. thermosulfata, Tm. perometabolis and Tm. intermedia (94.7 – 97.3% homology). Detailed results on various growth parameters were investigated for both moderate thermophilic strains, under various growth conditions (chemolithotrophic, heterotrophic, mixotrophic), concerning hydrogen uptake rate, biomass formation, sulfate production and utilization rates of organic compounds as well as growth rates. 16C was a very effective hydrogen oxidizer but could not utilize any of the sulfur ...